Teacher in Ki Hadjar Dewantara's Perspective - Syahrul, Syahrul; Didin Saefuddin; E. Bahruddin; Adian Husaini; Arif Budi Raharjo (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Teachers have shown their important role in building the Indonesian nation. Movements to educate the nation and fight the domination of the colonial education system have been carried out and initiated by the father of national education, Ki Hadjar Dewantara. Teachers must be properly trained and educated for quality, as well as quantity. Seeing the urgent need for teachers, Ki Hadjar Dewantara established Taman Guru which prepared cadres of pamong in various remote areas. This research aims to reveal Ki Hadjar Dewantara's response to Dutch colonial education with the regeneration of teachers and his conception of the figure of a teacher. This research uses qualitative research with primary data sources in the form of Ki Hadjar Dewantara's writings and documentation, while secondary sources are journals and newspapers or magazines relevant to the research. With a historical-philosophical approach, using content analysis, it was found that Ki Hadjar Dewantara saw that education had strayed far from its noble purpose. Education was used as a medium to perpetuate colonialism, so he established Taman Guru to be educated to become pamong who have an independent spirit, are independent and have high fighting power. Teachers according to Ki Hadjar Dewantara are educators, teachers, mentors, guides, caregivers and leaders who are respected, have inner and outer sincerity, simplicity, exemplary to foster the strength of children's nature, both as individuals and members of society to achieve the highest happiness.